The six certainties in uncertainty - Carranza Reyes, Odar Alexander (2020)
Throughout our existence we live preparing ourselves to provide our families with security; Thus, we seek in our professional development, a bias that offers it to us. Plainly, the constitutional institutions of the State are intended to provide legal predictability to citizens in their quest to provide security to their members. In order to prevent risks, insurance companies appeared dedicated to providing security, worth the redundancy, to those who, for some circumstance, contemplated in a contract, could see their health, properties or any particular interest threatened.So we wonder about what is the natural state of people? Will it be the security or uncertainty?